Islamic advertising: celebrating perfect moral vision - Mokhtar, Aida (2014)
Advertisements could be guided by the Facets of Model of Effects that encompass perception, emotional, cognition, association, persuasion, and behavior facets. Islam is a way of life. There are Islamic principles guiding communication including advertising. This paper discusses on advertising that is acceptable to Islam; one that celebrates perfect moral vision.